Evaluation of Alpha-1-acid Glycoprotein and Alpha-antitrypsin in Bronchoalveolarlavage Fluid for Extra-bronchial Tumor and Intra-bronchial Tumor in Lung Cancer - Hayder Hashim Alshalah (Journal of Global Pharma Technology, 2019)
Introduction: Lung cancer is one of the most common malignant tumors and the leading cause of cancer-related death worldwide. Aim of study: to evaluate of proteins (ALpha1 antitrypsin and alpha1 acid glycoprotein) in BALF in extra –bronchial Tumor and intra- bronchial Tumor of lung cancer. Material and method: this study was carried on 40 patients with lung cancer after they have bronchoscopy.  26 patients intra  -bronchial tumor in  BALF  (this is wash area of tumor when was be inside of bronchial)   14 patients extra –bronchial tumor in  BALF(this is wash area of tumor when was be outside of bronchial ) , detection (Alpha_1_antitrypsine,Alpha 1 acid glycoprotein )  in BALF were measure by Mispa Auto-analyzer Nephelometric immunoassay method).Result we found statistical significant between groups intra &extra - bronchial tumor  to each proteins .Our study also showed that at  a cut-off  to A1AT& ,A1AGthey  has a sensitivity, specificity, positive predictive value and negative predictive value of(100 ng/ml,100%,92 %,66.6%,100%respectively with an area under the ROC of A1AT .820) ,and (AGP, 70ng/ml, 100%93.3%,%50, 100%,)  respectively with an area under the ROC of AGP .745). Conclusion: A1AT & AGP are reliable markers to diagnosis extra &intra bronchia_ tumor in BALF for lung cancer.